Pengaruh Kompetensi dan Lingkungan Kerja terhadap Kinerja Pegawai - Muhammad Putra Lumaela; P. Sahetapy; Hendry Selanno (Jurnal Syntax Admiration, 2024)
The study of employee performance continues to be a major focus of human resource experts and practitioners. Various influential factors have been analyzed in relation to efforts to improve performance. Various aspects have been explored, both from the organizational and individual side, with various perspectives resulting in diverse findings. The focus of the study aimed to understand the impact of competencies and working conditions on employee outcomes. The approach in the study uses quantitative correlation which examines cause-and-effect relationships. The study population consisted of 96 employees of the Maluku Province Bawaslu, which was also used as the research sample (saturated sample). The instrument used has gone through validity and reliability testing, which then the data is analyzed using multiple linear regression methods. The study findings show that competence and work environment have a positive and significant impact on employee performance. This suggests that employees who are more competent and work in better working conditions tend to have better performance. The path analysis and discussion conducted in the study also supported these findings, concluding that competence working conditions have a positive and meaningful impact on employee performance, thus reinforcing the conclusion that these two factors are important in improving employee performance.